The school for good mothers eaudiobook A novel. - Chan, Jessamine (Simon & Schuster Audio, 2022)
Longlisted for the PEN/Hemingway Award for Debut Novel Longlisted for the 2023 Carnegie Medal for Excellence Shortlisted for The Center for Fiction 2022 First Novel Prize Selected as One of Barack Obama's Favorite Books of 2022! In this New York Times bestseller and Today show Read with Jenna Book Club Pick, one lapse in judgement lands a young mother in a government reform program where custody of her child hangs in the balance, in this "surreal" ( People ), "remarkable" ( Vogue ), and "infuriatingly timely" ( The New York Times Book Review ) debut novel. Frida Liu is struggling. She doesn't have a career worthy of her Chinese immigrant parents' sacrifices. She can't persuade her husband, Gust, to give up his wellness-obsessed younger mistress. Only with Harriet, their cherubic daughter, does Frida finally attain the perfection expected of her. Harriet may be all she has, but she is just enough. Until Frida has a very bad day. The state has its eye on mothers like Frida. The ones who check their phones, letting their children get injured on the playground; who let their children walk home alone. Because of one moment of poor judgement, a host of government officials will now determine if Frida is a candidate for a Big Brother-like institution that measures the success or failure of a mother's devotion. Faced with the possibility of losing Harriet, Frida must prove that a bad mother can be redeemed. That she can learn to be good. An "intense" ( Oprah Daily ), "captivating" ( Today ) page-turner that is also a transgressive novel of ideas about the perils of "perfect" upper-middle class parenting; the violence enacted upon women by both the state and, at times, one another; the systems that separate families; and the boundlessness of love, The School for Good Mothers introduces, in Frida, an everywoman for the ages. Using dark wit to explore the pains and joys of the deepest ties that bind us, Chan has written a modern literary classic.